The Influence of Satisfaction on Telepharmacy Application Use in Indonesia - Mulyo Wiharto; Rina Anindita; Ety Nurhayati; Sumartono (Jurnal Penelitian Pendidikan IPA, 2026)
The study was conducted to describe user satisfaction of web-based technology applications (user satisfaction), the use of web-based technology applications (application use) and the influence of user satisfaction on application use. Data collection used a questionnaire in the form of a Google form distributed to 30 respondents. The results of the regression test on the user satisfaction and application use variables obtained a constant value (a) of 7.388 and a user satisfaction coefficient of 0.569 so that the regression model is: Y = a + bX or 7.388 + 0.569X. A positive constant value of 7.388 indicates a positive influence of the user satisfaction variable or if the user satisfaction variable increases, the application use variable will also increase. The regression coefficient X of 0.569 states that if user satisfaction increases by 1 unit, then application use (Y) will increase by 0.569 or 56.9%. The results of the regression test on the user satisfaction and application use variables also obtained an F count of 4.209 and a significance level of 0.007. These results also indicate that the regression equation can be used to predict the application use variable. User satisfaction can be used to measure the success of using information technology-based applications (application use) and has a strong influence on application use.